1994
DOI: 10.1063/1.356164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ion beam assistance on the microstructure of nonhydrogenated amorphous carbon

Abstract: Nonhydrogenated diamondlike carbon films have been prepared by dual ion beam sputtering and ion-beam-assisted magnetron. The assistance parameters—ion energy, ion mass, ion flux/atom flux—have been systematically varied, and the films have been characterized by Rutherford backscattering spectroscopy, high-resolution transmission electron microscopy, electron energy loss spectroscopy, positron annihilation spectroscopy, Raman spectroscopy, and nanoindentation. It was found that the density and the degree of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…For a microstructure of nonhydrogenated amorphous carbon during IBAD, a model has been proposed, where small graphitic clusters are embedded in a strongly disordered mixture of sp 2 and sp 3 hybridized carbon. 16 With increasing substrate temperatures, the chemical bonding configuration varies distinctly. At elevated growth temperatures of 700 and 600°C, well separated G and D lines appear and G peaks shift to high frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…For a microstructure of nonhydrogenated amorphous carbon during IBAD, a model has been proposed, where small graphitic clusters are embedded in a strongly disordered mixture of sp 2 and sp 3 hybridized carbon. 16 With increasing substrate temperatures, the chemical bonding configuration varies distinctly. At elevated growth temperatures of 700 and 600°C, well separated G and D lines appear and G peaks shift to high frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…This C-C signature, already observed in Si-C alloys with carbon excess, 42,50-53 corresponds certainly to a specific structure which could be described like a random covalent network of tetrahedral-trigonal bonding carbons with distorted bond angles and bond lengths. [54][55][56][57][58] As a matter of fact, at first, it has been shown 57 that in mixed sp 2 Ϫsp 3 bonded carbon layers, the overall Raman spectrum is dominated by the G component, because the cross section of the graphite stretching mode is much higher than that of the 1332 cm Ϫ1 diamond mode. Second, Raman spectrum calculations 54 have shown that the incorporation of a small amount of tetrahedral bonding atoms ͑5%-10%͒ into a sp 2 network produced a downward shift in the G peak.…”
Section: Raman Analysesmentioning
confidence: 99%
“…The band appearing in the 1300-1600 spectra region is related to C-C vibrational modes. This C-C signature already observed in Si-C alloys with carbon excess [24,[27][28][29][30] corresponds certainly to a specific structure which could be described like a random covalent network of tetrahedral-trigonal bonding carbons with distorted bond angles and bond lengths [31][32][33][34][35]. As a matter of fact, it shows that in mixed sp 2 -sp 3 bonded carbon layer, the overall Raman spectrum is dominated by the G component (E 2g Raman mode of perfect graphite crystal), because the cross section of the graphite stretching mode is much higher than that of the 1332 cm −1 diamond mode.…”
Section: Stucture Analysismentioning
confidence: 99%